Recommendations for the treatment of children with radiotherapy in low‐ and middle‐income countries (LMIC): A position paper from the Pediatric Radiation Oncology Society (PROS‐LMIC) and Pediatric Oncology in Developing Countries (PODC) working groups of the International Society of Pediatric Oncology (SIOP). (3rd January 2018) - Parkes, Jeannette; Hess, Clayton; Burger, Hester; Anacak, Yavuz; Ahern, Verity; Howard, Scott C.; Elhassan, Moawia; Ahmed, Soha; Ghalibafian, Mithra; Abbasi, Ahmed Nadeem; Qureshi, Bilal Mazhar; Zaghloul, Mohamed; et al.
Abstract: Pediatric radiotherapy is a critical part of pediatric oncology protocols and the quality of the radiotherapy may determine the future quality of life for long‐term survivors. Multidisciplinary team decision making provides the basis for high‐quality care. However, delivery of high‐quality radiotherapy is dependent on resources. This article provides guidelines for delivery of good quality radiation therapy in resource‐limited countries based on rational procurement and maintenance planning, protocol development, three‐dimensional planning, quality assurance, and adequate staff numbers and training.